Alan's big, scary teeth (Somerville, Massachusetts : Candlewick Press, 2016)
When Alan wakes up to discover his big, scary teeth are missing, he tries to be scary without them.
Keywords: Teeth -- Fiction; Alligators -- Fiction; Humorous fiction